The influence of basal lamina on the accumulation of acetylcholine receptors at synaptic sites in regenerating muscle (The Rockefeller University Press, 1984)
If skeletal muscles are damaged in ways that spare the basal lamina sheaths of the muscle fibers, new myofibers develop within the sheaths and neuromuscular junctions form at the original synaptic sites on them. At the regenerated neuromuscular junctions, as at the original ones, the muscle fiber plasma membrane is characterized by infoldings and a high concentration of acetylcholine receptors (AChRs). The aim of this study was to determine whether or not the synaptic portion of the myofiber basal lamina sheath plays a direct role in the formation of the subsynaptic apparatus on regenerating myofibers, a question raised by the results of earlier experiments. The junctional region of the frog cutaneous pectoris muscle was crushed or frozen, which resulted in disintegration and phagocytosis of all cells at the synapse but left intact much of the myofiber basal lamina. Reinnervation was prevented. When new myofibers developed within the basal lamina sheaths, patches of AChRs and infoldings formed preferentially at sites where the myofiber membrane was apposed to the synaptic region of the sheaths. Processes from unidentified cells gradually came to lie on the presynaptic side of the basal lamina at a small fraction of the synaptic sites, but there was no discernible correlation between their presence and the effectiveness of synaptic sites in accumulating AChRs. We therefore conclude that molecules stably attached to the myofiber basal lamina at synaptic sites direct the formation of subsynaptic apparatus in regenerating myofibers. An analysis of the distribution of AChR clusters at synaptic sites indicated that they formed as a result of myofiber-basal lamina interactions that occurred at numerous places along the synaptic basal lamina, that their presence was not dependent on the formation of plasma membrane infoldings, and that the concentration of receptors within clusters could be as great as the AChR concentration at normal neuromuscular junctions.